The ATLAS ReadOut System - Performance with first data and perspective for the future - Crone, Gordon; Della Volpe, D.; Gorini, B.; Green, B.; Joos, M.; Kieft, G.; Kordas, K.; Kugel, Andreas; Misiejuk, A.; Schroer, Nicolai; Teixeira-Dias, P.; Tremblet, L.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
The ATLAS ReadOut System (ROS) receives data fragments from ∼1600 detector readout links, buffers them and provides them on demand to the second-level trigger or to the event building system. The ROS is implemented with ∼150PCs. Each PC houses a few, typically 4, custom-built PCI boards (ROBIN) and a 4-port PCIe Gigabit Ethernet NIC. The PCs run a multi-threaded object-oriented application managing the requests for data retrieval and for data deletion coming through the NIC, and the collection and output of data from the ROBINs. At a nominal event fragment arrival rate of 75kHz the ROS has to concurrently service up to approximately 20kHz of data requests from the second-level trigger and up to 3.5kHz of requests from event building nodes. The full system has been commissioned in 2007. Performance of the system in terms of stability and reliability, results of laboratory rate capability measurements and upgrade scenarios are discussed in this paper.